Toward a Test of Wheeler's "Integrative Theory" in Six Union Election Cases - Wheeler, Hoyt; McClendon, John; Weikle, Roger (Relations industrielles / Industrial Relations, 1994)
Using data from six union certification election cases (three union wins and three union losses) in the United States, this study examines the phenomenon of unionization, drawing upon Wheeler's (1985) theory of industrial conflict. The comparative case study assessment suggests that a union win is related to employee deprivation, calculation as to union effectiveness, instrumentality perceptions, and attitudes about unions. In general, the results are somewhat supportive ofthe theory and suggest avenues for future research.